Variable Impedance Control Based on Target Position and Tracking Error for Rehabilitation Robots During a Reaching Task - Tang, Rongrong; Yang, Qianqian; Song, Rong (Frontiers in Neurorobotics, 2022)
To obtain an anthropomorphic performance in physical human-robot interaction during a reaching task, a variable impedance control (vIC) algorithm with human-like characteristics is proposed in this paper. The damping value of the proposed method is varied with the target position as well as the tracking error. The proposed control algorithm is compared with the impedance control algorithm with constant parameters (IC) and another variable impedance control algorithm, which is only changed with the tracking error (vIC-e). The different control algorithms are validated through the simulation study, and are experimentally implemented on a cable-driven rehabilitation robot. The results show that the proposed vIC could improve the tracking accuracy and trajectory smoothness, and reduce the interaction force at the same time.